Penatalaksanaan Terapi Bermain Meronce Manik-Manik Untuk Meningkatkan Konsentrasi Pada Anak Dengan Gangguan Pemusatan Perhatian dan Hiperaktifitas - Agung Mugi Destiana; Surati Ningsih (Indonesian Journal on Medical Science, 2022)
Attention Deficit Hyperactivity Disorder (ADHD) is a disorder in which a child exhibits hyperactive, impulsive, and/or no-attention behavior that is consistent with his or her age. Higher ADHD incidence rates occur in primary school-aged children than in adolescents and adults. ADHD Pravalence in school-age children in the United States of 8-10%. The purpose of this study was to incrase the concentration of children with ADHD. The type of this research is descriptive case study using case study research approach in ADHD child. The subjects of this study were children with a number of 2 people taken with non probalility sampling technique with purposive sampling approach. The results of this study indicate that of the 2 patients aged 10 years, playing up uncontrolled, often failing to pay attention, not listening to the teacher's words, often avoiding an activity, being cool with their own activities, often against teacher commands, not completing tasks. So it can be enforced the risk of developmental delay associated with ganggua behavior (attention deficit). The researchers performed therapeutic action of meronce beads to increase the concentration for 10 x 45-60 minutes, obtained the evaluation results 1 of 2 subjects had increased concentration from 2 minutes to 6 minutes during meronce beads. Such action is effective in efforts to increase concentrations in GPPH children.